Role of Islamic Law in the Efficient Management of Debt in Nigeria - Zubair, Aishat Abdul-Qadir; Muhammed-Mikaaeel, Ahmed Abiodun (Jurnal Hukum Novelty, 2023)
Introduction to The Problem: Nigeria's Q4 2021 Real GDP reached N20.33 trillion, with a 3.98% YoY growth, marking the fifth consecutive quarter of positive growth post-2020 recession. Despite this, the economy is deemed in crisis. Concerningly, the government is accumulating more debt to service existing obligations, posing sustainability issues and conflicting with Shari’ah wealth management principles.Purpose: This study aims to analyze the impact of Islamic law on effective debt management in Nigeria, specifically addressing the consequences of economic crises that result in substantial national borrowing. Additionally, it aims to highlight Sharia jurisprudence as a viable solution to alleviate Nigeria's economic challenges.Design/Methodology/Approach: The Methodology employed in this study is purely doctrinal method of legal research. Hence, the study places reliance principally on the available literature by which the study explores relevant materials such as text books, journals and internet facilities. Importantly, the study finds most useful the primary sources of Shari’ah which are the Qur’an and Sunnah as well as the secondary sources which include Qiyas and Ijma’.Findings: The study finds that the economic crisis which Nigeria has found itself as a result of the multiplier effect of excessive public borrowing cannot be divorced from the adoption of the conventional economic system. The result reveals further that Islamic law plays significant roles in the efficient management of debt as was confirmed in the Malaysian Shari’ah compliant public debt management practices. The study proposes, by way of recommendation, the practice of Islamic Wealth Management to cushion the effect of the deficit budgets and the onerous debts on Nigeria and increase investment activities with a view to impacting positively on the country’s GDP. The study is therefore most relevant to the policymakers in the Ministry of Finance, Debt Management Office, as well as the Lawmakers in the country.Paper Type: Research Article